2014
DOI: 10.1155/2014/642589
|View full text |Cite
|
Sign up to set email alerts
|

Double Grazing Periodic Motions and Bifurcations in a Vibroimpact System with Bilateral Stops

Abstract: The double grazing periodic motions and bifurcations are investigated for a two-degree-of-freedom vibroimpact system with symmetrical rigid stops in this paper. From the initial condition and periodicity, existence of the double grazing periodic motion of the system is discussed. Using the existence condition derived, a set of parameter values is found that generates a double grazing periodic motion in the considered system. By extending the discontinuity mapping of one constraint surface to that of two constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Bernard [7] analyzed the slip bifurcations of n-dimensional piecewise smooth dynamical systems, gave the corresponding discontinuous mapping, and derived the complete expression of the grazing-induced bifurcation normal form mapping. Li [8] considered a two-degree-of-freedom impact oscillator with symmetrical rigid constraints, found the dynamic behavior induced by grazing bifurcation numerically. Zhang [9] derived the discontinuous maps of a rub-impacting rotor system, used the sequence limit theory to analyze the bifurcation situation induced by grazing of the rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…Bernard [7] analyzed the slip bifurcations of n-dimensional piecewise smooth dynamical systems, gave the corresponding discontinuous mapping, and derived the complete expression of the grazing-induced bifurcation normal form mapping. Li [8] considered a two-degree-of-freedom impact oscillator with symmetrical rigid constraints, found the dynamic behavior induced by grazing bifurcation numerically. Zhang [9] derived the discontinuous maps of a rub-impacting rotor system, used the sequence limit theory to analyze the bifurcation situation induced by grazing of the rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…di Bernardo et al [23] extended the results presented in [17] to n-dimensional piecewise-smooth systems and derived normal form maps for grazing bifurcation. For additional literature about grazing bifurcation, see, e.g., [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Blazejczyk-Okolewska et al [25] studied the dynamics of two mechanical oscillators coupled by impacts and observed the anti-phase synchronization phenomenon when the distance between these oscillators exceeded some critical thresholds. In [26][27][28][29], the dynamics of multi-degree-of-freedom vibro-impact systems has been studied by using numerical simulations and qualitative analysis. This paper will use the physical model in [25] to study the dynamics and the synchronization of impulsively coupled oscillators under variations of amplitude and frequency of external excitation.…”
Section: Introductionmentioning
confidence: 99%